Composition and Diversity Variation of Avifauna, along Different Vegetative Habitat Types in a Human-Modified Area, University of Kelaniya, Sri Lanka - Bellanthudawa, B. K. A.; Nawalage, N. M. S. K.; Subanky, S.; Panagoda, P. A. B. G.; Weerasinghe, H. W. G. A. S.; Tharaka, L. K. D. N.; Handapangoda, H. M. A. K.; Silva, H. K. A. D.; Dissanayake, D. M. S. N.; Abeywickrama, M. S. J. (International Journal of Zoology, 2019)
Role of conservation of birds has been least considered during modification of vegetative habitats, in studies conducted on birds in protected areas and urban landscapes in Sri Lanka. The present study was intended to assess the relationship between landscape and the composition and distribution of avifauna in University of Kelaniya, a human-modified area. The study was conducted selecting 8 habitats including open ground, low, moderately, and highly wooded habitats. A survey was conducted from 0530 to 0730 hr in the morning and 1630-1830 hr in the evening from August to December 2016 ensuring eight sampling events at each habitat. Point counting method (15 m radius) was used along a 100 m line transect. Species diversity parameters were analyzed. Principal Component Analysis (PCA) was performed to characterize the habitats with bird species. A total of 40 species were recorded. Species richness (r = 27) and species heterogeneity (H′ = 3.09) were the highest in Mee amba sevana habitat while species evenness (J = 0.977) was the highest in medical center area habitat. Total abundance (n = 135) was recorded in Saiba ground. Asian brown flycatcher (Saiba ground, medical center area, Mee amba sevana, Girls’ Hostel complex, and English language unit habitats) and white-bellied drongo (Saiba ground, medical center area, Girls’ Hostel complex, English language unit, and Thal weta premises) were widely distributed (z > 0, Kruskal-Wallis, Minitab 14). The second largest distribution was recorded by black-hooded oriole, blue-tailed bee-eater, cattle egret, feral pigeon, brown-headed barbet, red-vented bulbul, and rose-ringed parakeet within four habitats (z > 0, Kruskal-Wallis). According to the PCA, Saiba ground habitat was categorized by open ground dwelling birds, and Mee amba sevana was characterized by frugivorous birds, while Girls’ Hostel complex habitat was characterized by carnivorous birds. Comparatively, medical center area habitat contributes to the highest species diversity with many flowering and fruiting trees while providing sufficient food resources and high floral structural complexity. Recorded avifaunal community composition ensures considerable conservation value to university premises of Kelaniya. Awareness and monitoring programs are recommended for sustainable conservation of bird species in Kelaniya.